ChemInform Abstract: Formation of [Bi11]3‐, a Homoatomic, Polycyclic Bismuth Polyanion, by Pyridine‐Assisted Decomposition of [GaBi3]2‐. Issue 29 (22nd July 2014) - Weinert, Bastian; Eulenstein, Armin Rainer; Ababei, Rodica; Dehnen, Stefanie
Abstract The binary Zintl anion [GaBi3]2‐ decomposes under oxidative coupling of pyridine and release of H2 to form the polycyclic bismuth polyanion [Bi11]3‐, which exhibits the [P11]3‐ "ufosan" structure.